2014
DOI: 10.3389/fenvs.2014.00012
|View full text |Cite
|
Sign up to set email alerts
|

Snails promote methane release from a freshwater lake ecosystem

Abstract: Benthic fauna, as ecosystem engineers, can strongly affect microbial-driven ecosystem biogeochemical cycling. However, the effects of benthic fauna, especially epifauna, on CH 4 cycling remain still elusive. In this study, CH 4 effluxes were both measured along a gradient of snail density in a freshwater lake ecosystem in China, and monitored in manipulated laboratory microcosms with and without snails. Field CH 4 efflux was significantly increased with snail density. Likewise, the stimulating effects of fresh… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 26 publications
0
4
0
Order By: Relevance
“…The mean annual temperature and precipitation are 17°C and 1636 mm, respectively. The Poyang Lake wetland has a high fluctuation of seasonal water levels between the flood and dry seasons (Xu et al, 2014 ). In the dry season, the surface area of the lake shrinks to less than one-tenth of the area in the flood season.…”
Section: Methodsmentioning
confidence: 99%
“…The mean annual temperature and precipitation are 17°C and 1636 mm, respectively. The Poyang Lake wetland has a high fluctuation of seasonal water levels between the flood and dry seasons (Xu et al, 2014 ). In the dry season, the surface area of the lake shrinks to less than one-tenth of the area in the flood season.…”
Section: Methodsmentioning
confidence: 99%
“…In freshwater ecosystem, the snails (Mollusca: Gastropoda) carry out multiple functional roles, many of which are attributable to the shell. Apart from mechanical strength and protection, the shells of freshwater snails facilitate the anchorage of various microbes and periphytons .…”
Section: Introductionmentioning
confidence: 99%
“…Macrophyte stands also provide a habitat for several aquatic organism groups that produce CH 4 via classic methanogenesis in an otherwise aerobic water column. Marine zooplankton produces CH 4 in anoxic microzones (De Angelis and Lee 1994; Schmale et al 2018) and snails have been shown to promote CH 4 release from freshwater lakes (Xu et al 2014). Provision of shelter for zooplankton and macroinvertebrates has been observed for marine kelps (Pakhomov et al 2002), seagrass stands (Robertson et al 1988), and freshwater submerged macrophytes (Timms and Moss 1984).…”
Section: Potential Of Submerged Macrophytes For Ompmentioning
confidence: 99%